Multimodal monitoring intracranial pressure by invasive and noninvasive means - Fabiano Moulin de Moraes; Erica Navarro Borba Adissy; Eva Rocha; Felipe Chaves Duarte Barros; Flávio Geraldo Rezende Freitas; Maramelia Miranda; Raul Alberto Valiente; João Brainer Clares de Andrade; Feres Eduardo Aparecido Chaddad-Neto; Gisele Sampaio Silva (Scientific Reports, 2023)
Abstract Although the placement of an intraventricular catheter remains the gold standard method for the diagnosis of intracranial hypertension (ICH), the technique has several limitations including but not limited to its invasiveness. Current noninvasive methods, however, still lack robust evidence to support their clinical use. We aimed to estimate, as an exploratory hypothesis generating analysis, the discriminative power of four noninvasive methods to diagnose ICH. We prospectively collected data from adult intensive care unit (ICU) patients with subarachnoid hemorrhage (SAH), intraparenchymal hemorrhage (IPH), and ischemic stroke (IS) in whom invasive intracranial pressure (ICP) monitoring had been placed. Measures were simultaneously collected from the following noninvasive methods: optic nerve sheath diameter (ONSD), pulsatility index (PI) using transcranial Doppler (TCD), a 5-point visual scale designed for brain Computed Tomography (CT), and two parameters (time-to-peak [TTP] and P2/P1 ratio) of a noninvasive ICP wave morphology monitor (Brain4Care[B4c]). ICH was defined as a sustained ICP > 20 mmHg for at least 5 min. We studied 18 patients (SAH = 14; ICH = 3; IS = 1) on 60 occasions with a mean age of 52 ± 14.3 years. All methods were recorded simultaneously, except for the CT, which was performed within 24 h of the other methods. The median ICP was 13 [9.8–16.2] mmHg, and intracranial hypertension was present on 18 occasions (30%). Median values from the noninvasive techniques were ONSD 4.9 [4.40–5.41] mm, PI 1.22 [1.04–1.43], CT scale 3 points [IQR: 3.0], P2/P1 ratio 1.16 [1.09–1.23], and TTP 0.215 [0.193–0.237]. There was a significant statistical correlation between all the noninvasive techniques and invasive ICP (ONSD, r = 0.29; PI, r = 0.62; CT, r = 0.21; P2/P1 ratio, r = 0.35; TTP, r = 0.35, p < 0.001 for all comparisons). The area under the curve (AUC) to estimate intracranial hypertension was 0.69 [CIs = 0.62–0.78] for the ONSD, 0.75 [95% CIs 0.69–0.83] for the PI, 0.64 [95%Cis 0.59–069] for CT, 0.79 [95% CIs 0.72–0.93] for P2/P1 ratio, and 0.69 [95% CIs 0.60–0.74] for TTP. When the various techniques were combined, an AUC of 0.86 [0.76–0.93]) was obtained. The best pair of methods was the TCD and B4cth an AUC of 0.80 (0.72–0.88). Noninvasive technique measurements correlate with ICP and have an acceptable discrimination ability in diagnosing ICH. The multimodal combination of PI (TCD) and wave morphology monitor may improve the ability of the noninvasive methods to diagnose ICH. The observed variability in non-invasive ICP estimations underscores the need for comprehensive investigations to elucidate the optimal method-application alignment across distinct clinical scenarios.